Evaluation of Percutaneous Intradiscal Amniotic Suspension Allograft in a Rabbit Model of Intervertebral Disc Degeneration. Issue 6 (15th March 2019) - Luo, Tianyi David; Vines, Jeremy B.; Zabarsky, Zachary K.; Mowry, Katie C.; Marquez-Lara, Alejandro; Jinnah, Alexander H.; Ma, Xue; Berwick, Benjamin W.; Willey, Jeffrey S.; Smith, Thomas L.; Li, Zhongyu; O'Gara, Tadhg J.
Abstract : Study Design: A laboratory study using a rabbit annular puncture model of intervertebral disc degeneration (IDD). Objective: The aims of this study were to assess whether an amniotic suspension allograft (ASA) containing particulated human amnion and amniotic fluid derived cells regains intervertebral disc height and morphology and improves histologic scoring in a rabbit model of IDD. Summary of Background Data: In contrast to current surgical interventions for IDD, in which the primary goal is to relieve symptomatic pain, one novel strategy involves the direct injection of anabolic cytokines. Current therapies for IDD are limited by both the short half-life of therapeutic proteins and general decline in anabolic cell populations. Methods: Intervertebral discs in New Zealand white rabbits were punctured using 18-gauge needle under fluoroscopic guidance. Four weeks post-puncture, two groups of rabbits were injected with either ASA or a vehicle/sham control, while a third group was untreated. Weekly radiographs were obtained for 12 weeks to assess disc height index (DHI). Magnetic resonance imaging (MRI) T2 relaxation time was evaluated at weeks 4 and 12 to assess morphological changes. Histologic sections were evaluated on a semi-quantitative grading scale. Results: Before treatment at week 4, DHIs and normalized T2 relaxation times between the three groups were not significantly different. At week 12, ASA-treated rabbits exhibited significantly greater DHIs and MRI T2 relaxation times than vehicle and untreated control groups. The ASA group had higher mean histologic score than the vehicle group, which demonstrated extensive fiber disorganization and delamination with reduced proteoglycan staining on histology. Conclusion: Minimally invasive intervention with intradiscal injection of ASA was successful in reducing IDD in a reproducible rabbit model, with significant improvement in disc height and morphology when compared with vehicle and untreated control groups on radiographic and MRI analyses. Level of Evidence: N/A Abstract : Current therapies for intervertebral disc degeneration are limited by general decline in anabolic cell populations. Using a rabbit model, we evaluated the efficacy of amniotic suspension allograft to treat induced intervertebral disc degeneration. Intradiscal amniotic suspension allograft treatment resulted in partially regained disc space and improvement in disc morphology.